1992
DOI: 10.1111/j.1432-1033.1992.tb17346.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution conformation of human neuropeptide Y by 1H nuclear magnetic resonance and restrained molecular dynamics

Abstract: The solution structure of human neuropeptide Y has been solved by conventional two-dimensional NMR techniques followed by distance-geometry and molecular-dynamics methods. Thc conformation obtained is composed of two short contiguous ol-helices comprising residues 15 -26 and 28 -35, linked by a hinge inducing a 100' angle. l h e first helix (15-26) is connected to a polyproline stretch (residues 1 -10) by a tight hairpin (residues 11 -14). The helices and thc polyprolinc stretch are packed together by hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 20 publications
3
69
0
Order By: Relevance
“…Furthermore, the (PXX). spacing of proline residues is consistent with the formation of an extended polyproline II helix (29), a structure that has been shown to interact with the conserved hydrophobic groove common to the known SH3 structures (30).…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the (PXX). spacing of proline residues is consistent with the formation of an extended polyproline II helix (29), a structure that has been shown to interact with the conserved hydrophobic groove common to the known SH3 structures (30).…”
Section: Discussionmentioning
confidence: 64%
“…A 1H-NMR study on neuropeptide Y monomers in water confirmed the presence of the hairpin loop based on a series of long range nuclear Overhauser effects (NOEs) between the N-and Cterminal segments (Darbon et al, 1992). The secondary structure obtained by NMR is in agreement with the model of Allen et al (1987), as well as with the results obtained from structure activity relationships, which have suggested a close contact between the N-and C-terminal segments (Beck et al, 1989a, b;Beck-Sickinger et al, 1990a, b;1992a, b).…”
Section: Introductionmentioning
confidence: 94%
“…p892 and p931) are indicated by the arrows. Structural analysis of proline-rich regions in other proteins (28,29), where proline is present as every third residue, suggests that these regions adopt a conformation with 3 residues per turn, known as the polyproline II (PP II) helix, with a 3.1-Å rise/residue (30). By analogy it is predicted that the P-region of SA I/II, which also contains frequently repeating (PXX) n motifs, may also adopt a PP II helix-like conformation (31).…”
Section: Discussionmentioning
confidence: 99%